Budgeting basics and beyond - Shim, Jae K; Siegel, Joel G; Shim, Allison I (Wiley corporate F & A., 2011)
"Budgeting Basics and Beyond, 4th Edition is a practical, easy-to-use problem-solver and up-to-date reference tool for today's financial and nonfinancial managers in public practice and private industry. It is packed with case studies, illustrations, exhibits, forms, checklists, graphs, samples, and worked-out solutions to a wide variety of budgeting, planning, and control problems. It is a truly valuable resource guaranteed to make the budgeting process effective and hassle-free for all managers who use it. The new edition includes new cost cutting strategies, software packages updates, cloud computing nd, new use of Excel for exponential smoothing, Minitab and SPSS, and updates on cash flow software. The book also includes financial planning and new types of financial modeling, variance analysis, Web-based budgeting, active budgeting illuminating "what-if" analyses throughout, spreadsheet applications, break-even analysis, project analysis, and capital budgeting"--